2005
DOI: 10.1111/j.1365-2036.2005.02512.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference on the symptoms, health‐seeking behaviour, social impact and sleep quality in irritable bowel syndrome: a Rome II‐based survey in an apparent healthy adult Chinese population in Taiwan

Abstract: SUMMARYBackground: Little is known about the gender effect on irritable bowel syndrome in Asia. Aim: To assess the gender difference in Chinese subjects with irritable bowel syndrome meeting Rome II criteria. Methods: Irritable bowel syndrome was identified from an apparently healthy adult population receiving a routine health maintenance program (n ¼ 2018). Results: Female gender is not a factor associated with irritable bowel syndrome or irritable bowel syndromerelated health care-seeking behaviour. Female i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 55 publications
1
34
1
1
Order By: Relevance
“…As in previous studies [2,3,22,24,32,37], other organic gastrointestinal diseases, such as gallbladder stones, peptic ulcers, and reflux esophagitis, were found in the IBS patients in the present study. However, there were no differences in the prevalence rates of these diseases between the IBS (+) and (À) groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As in previous studies [2,3,22,24,32,37], other organic gastrointestinal diseases, such as gallbladder stones, peptic ulcers, and reflux esophagitis, were found in the IBS patients in the present study. However, there were no differences in the prevalence rates of these diseases between the IBS (+) and (À) groups.…”
Section: Discussionsupporting
confidence: 87%
“…There are data that show differences in IBS prevalence according to gender, ethnicity, age, region, etc. [2,3,6,17,[22][23][24][29][30][31]. Therefore, these differences may result from real population differences.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in other studies conducted in Asian countries, including Korea, IBS was reported to occur in men more often than in women. [42][43][44] The reason for the discrepancy in the occurrence of IBS according to sex between Western and Asian countries is unclear but could be the result of cultural, psychosocial, or healthcare access issues, rather than purely sex-related physiologic differences. 45 The mechanism underlying the relationship between the SE type and IBS is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The reported IBS prevalence is determined by a number of factors including subject gender, used criteria, questionnaires, study methods, locations, geographical characters, cultural and social backgrounds, and ethnicity [3,8,9,11] . Clinically, IBS is not only confined to the colon but may also extend to other organs and systems since IBS individuals usually have multiple comorbidities such as dyspepsia, gastro-esophageal reflux disease, interstitial cystitis, fibromyalgia, chronic fatigue, insomnia, headache/migraine and psychiatric disturbances [12][13][14][15][16][17][18] . Owing to the commonly associated somatic comorbidities and high level of psychiatric disturbances, IBS subjects often have absenteeism, reduced quality of life (QoL) and multiple healthcare seeking behaviors, which lead to great social and economic burdens [13,16,[19][20][21] .…”
Section: Introductionmentioning
confidence: 99%